Strategi Publikasi PT Kereta Api Indonesia (Persero) Daerah Operasional 1 Jakarta Dalam Menjaga Stabillitas Reputasi Perusahaan - Suryaning hayati; Abdul Rahmat; Nurul Aidin (Jurnal Visi Komunikasi, 2020)
business competition is not only measured by the level of sales and product image. However, there is another thing that is more principle, inherent, and fundamental, namely reputation. This study aims to determine the Publication Strategy of PT Kereta Api Indonesia (Persero) Operational Region 1 Jakarta in Maintaining the company's reputation stability. The focus in research is the publication strategy in terms of the aspects of publication goals, publication objectives, message content and strategic message content, impact of publication exposure, media strategy, and evaluation methods. Research with constructivism paradigm with descriptive method. Primary data were obtained from in-depth interviews with key informants, Senior Manager of Public Relations and Public Relations staff informants.The purpose of publication is education to gain public understanding of company programs and policies. The message content and strategic message content to construct messages are to convey the main basis for why the policy should be carried out, why the program must be carried out, and convey about its goals and benefits for the community; The expected impact of publication exposure is a positive image according to the community. The media strategy taken is to build personal relationships, ensure information disclosure, commitment to response speed, accommodate media data needs, and facilitate the media in publishing news;